Conservative Management Techniques for Ideal Grooming and Upbringing of Downs Syndrome Children - Ibtesam-E-Fajar, Taimur Khalil Sheikh, Huma Bashir Janjua, Daniyal Ahmed, Iman Baig, Sundus Asghar Baig, Aamna Khokhar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Down syndrome are slow learners having mild to moderate intellectual disability with co-morbidities, we need to pay special attention on conservative management techniques like early intervention programs, speech therapies, physiotherapies, exercises, sports, schooling and education etc. to make these children intellectual compatible for a normal life. Aim: To identify the conservative management techniques for improving the quality of life for down syndromes. Methodology: A descriptive cross-sectional survey (designed after literature search) was conducted from the parents of Down Syndromes at special children’s schools in Islamabad and Rawalpindi according to inclusion criteria i.e., school going down syndromes and residents of Islamabad and Rawalpindi, in an interactive counselling session conducted by authors in collaboration with pediatrician, keeping the questionnaire anonymous. Results: For the management of Down Syndromes, out of 44 parents, 36(81.8%) agreed on home based teaching, 34(77.3%) agreed on exercise, gym and sports for down syndromes. Around 38(86.4%) agreed on speech therapy and social interactions, 31(70.5%) parents agreed on controlled and healthy diet and 34(77.3%) parents said brain storming and learning new things should be in practice for down syndromes. Conclusion: Down syndrome is a complex condition requiring a multi-disciplinary team of professionals to manage the myriad of problems faced by the patients. Aside from these, a vital role is played by parents, teachers & the community itself in taking care of these special individuals. Also, Down syndrome is characterized by learning disabilities as its hallmark feature but their learning abilities can be improved through certain conservative management techniques.